HUBUNGAN ANTARA PENYALAHGUNAAN JENIS NARKOBA DENGAN GANGGUAN KESEHATAN REPRODUKSI DI LEMBAGA PEMASYARAKATAN KOTA BENGKULU TAHUN 2012 - Putri, Niki Rian (Politeknik Kesehatan Kemenkes Bengkulu, 2012)
Drug cases in Bengkulu in 2011 are 246 cases, 6 of 10 abusers in Bengkulu City Correctional Prison have reproductive health disruption. Abuse, among others, may affect the reproductive hormones interfere with testosterone or estrogen hormone metabolism. The aim of this research is to determine the relationship of the drug abuse with reproductive health disorders in Bengkulu City Correctional Prison in 2012. This study uses analytic survey with cross sectional approach. The population of this study are drug abuser in Bengkulu City Prison with 134 samples (total sampling). Retrieval of data by distributing questionnaires then performed univariate analysis with frequency distributions and bivariate analysis with Chi-square.The results of this study indicate that the majority (59.7%) of respondents misuse psychotropic drug, and almost all events (76.2%) of respondents experienced reproductive health disruption. Chi-square test results obtained ρ<0,05, which means there is a significant association between drug abuse with reproductive health disruption with a value of OR = 2.384.Officers are expected to do the treatment for detainees and inmates who have reproductive health disruption by reactivating health care center and doing regular urine tests.